2022
DOI: 10.20525/ijrbs.v11i10.2103
|View full text |Cite
|
Sign up to set email alerts
|

Theological inquest of the teaching of life sciences within the Muslim schools

Abstract: The teaching of life sciences within the Islamic culture was observed in this investigation by instructors at the Association of Muslim Schools in the KZN region. The following question served as the basis for the investigation: Do Islamic schools teach life sciences from an Islamic perspective? The Association of Muslim Schools gave its approval after receiving ethical scrutiny. A questionnaire, interviews, and observations were used to gather data. The analysis of the data was conducted using an inductive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In such cases, they have to seek alternative learning materials to accommodate their students' needs. These alternative materials may not be as perfect as the original resources, but they serve as substitutes (Adu & Adu, 2014;Ayua, 2011;Dhurumraj & Moola, 2023). Studies have revealed that in many developing countries, teaching and learning materials are scarce and expensive, and even when acquired, they are severely insufficient to accommodate the growing number of students in schools (Ayua, 2011;Obidike, 2021;Makokha, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In such cases, they have to seek alternative learning materials to accommodate their students' needs. These alternative materials may not be as perfect as the original resources, but they serve as substitutes (Adu & Adu, 2014;Ayua, 2011;Dhurumraj & Moola, 2023). Studies have revealed that in many developing countries, teaching and learning materials are scarce and expensive, and even when acquired, they are severely insufficient to accommodate the growing number of students in schools (Ayua, 2011;Obidike, 2021;Makokha, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the ability to improvise is a distinguishing feature of exceptional teaching. It allows educators creating dynamic, engaging, and impactful learning experiences for their students (Dhurumraj & Moola, 2023;Mzinga & Onyango, 2021;Ngussa & Singolyo, 2018;Ramaila, 2022). In the context of classroom teaching, teachers must be proficient in improvisation, and their experience only enhances their ability to respond to and navigate unpredictable educational scenarios that require immediate attention and action (Dhurumraj & Moola, 2023;Ramaila, 2022;Ramothwala & Ramaila, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations